Investigation of a wheel liquid desiccant cooling system performance via ANSYS CFX - Mohd Anas Mohd Sabri; Loh, Chow Qin; Nor Kamaliana Khamis; Meor Iqram Meor Ahmad; Wan Aizon W. Ghopa (Penerbit Universiti Kebangsaan Malaysia, 2024)
A liquid desiccant cooling system is an alternative air-conditioning system with significant energy-saving potential. This system is commonly used in the industrial sector, such as in dehumidifiers. The key component of the liquid desiccant cooling system is its dehumidification performance. Therefore, a study on a liquid desiccant dehumidifier has been conducted to predict its performance using computational fluid dynamics analysis. In these simulations, the effects of the temperature of the liquid desiccant and the velocity of air flow on the absorption process between the liquid desiccant and air were studied. The same applies to the velocity profile, which helps determine the airflow pattern within the dehumidifier. The model was constructed using ANSYS FLUENT and Autodesk Inventor. The model is the rotary desiccant wheel dehumidifier which was used to dehumidified the air.. ANSYS CFX was used for simulating the velocity profile to achieve the airflow pattern in the dehumidifier. The volume of fluid was selected as the multiphase method for the second simulation process. The temperature and mass fraction of water were monitored within the air during the counterflow simulation between the liquid desiccant and the air. The liquid desiccant chosen for this study was LiCl. The simulations were conducted at specific air velocities, and the behavior within the dehumidifier was observed. The analysis results revealed that the air entering the rotary desiccant wheel dehumidifier experienced a drop in velocity after passing through the desiccant wheel in the middle. Additionally, turbulence occurred after the air passed through the wheel and the dehumidifier’s wall. Based on these findings, the design of an optimal dehumidifier and the selection of an appropriate air velocity for cooling can be carried out.